Hemodynamic changes under balloon occlusion of hepatic artery: predictor of the short-term therapeutic effect of balloon-occluded transcatheter arterial chemolipiodolization using miriplatin for hepatocellular carcinoma - Asayama, Yoshiki (Springerplus, 2016)
To clarify the hemodynamic changes under balloon occlusion of the hepatic artery and to identify predictors of the short-term therapeutic effect (TE) after balloon-occluded transcatheter arterial chemoembolization using miriplatin (B-TACE) for hepatocellular carcinoma (HCC). Tumor variables and angiographic data were collected for 35 nodules (29 patients) with a B-TACE for HCC. Lesions were classified into three groups based on the balloon-occluded CT hepatic arteriography (BO-CTHA) results: Group A, presence of corona enhancement; Group B, absence of corona enhancement; Group C, decreased perfusion or perfusion defect compared to standard CTHA. Objective response was defined as TE3/4, and poor TE as TE1/2, evaluated by response evaluation criteria in cancer of the liver at 1–4 months after the procedure. Univariate analysis revealed that proximal level of balloon occlusion, intratumoral lower CT values immediately after treatment and BO-CTHA findings were significantly correlated with poor TE (p = 0.034, 0.037, and 0.003, respectively). Multivariate logistic analysis identified the Group C as a significant factor associated with the worse short term TE (odds ratio 8.34; 95 % confidence interval 1.49–68.8). Partial or complete perfusion defect on BO-CTHA was an independent factor associated with poor therapeutic effect.